Development networks and urban growth in small cities. (January 2020) - Varna, Georgiana; Adams, David; Docherty, Iain
Real estate development is an intensely social process dependent on rich networks of relations between public and private sector actors. Previous work has explored how far such relations are formalised in large cities through shared coalitions of interest intended to promote urban growth. Relatively little attention has been given to networks in smaller cities, which is the concern of this paper. Drawing on detailed research in a small Scottish city, the paper explores how its local network was characterised by strong reliance on network construction and reproduction through trust and reputation. Significantly, within such local networks, competition and collaboration can exist side by side, without subsuming normal tensions into consistent agendas or formally defined 'partnerships'. Controlling land for urban expansion provides a particular focus for these tensions, since it can allow certain interests to gain network dominance. These findings raise important concerns around whether small cities should rely on informal networks to promote growth instead of constructing formal coalitions that may attract more externally based actors. Such choices have profound implications for the capacity and transparency of development networks, and thus for the accountability of the urban development process.